2020 special issue: Twenty years of breast reconstruction: Past, present, and future. Issue 1 (23rd January 2020) - Spiegel, Aldona J.; Kania, Katarzyna; Hamilton, Kristy L.
Abstract: Breast reconstruction has evolved in the last 25 years to provide women with better autologous and implant‐based options. The general trends of breast reconstruction have shifted to skin and nipple‐areolar complex preservation, resulting in improved aesthetics and patient satisfaction. Autologous reconstruction has made a dramatic movement toward microsurgical reconstruction by free tissue transfer and has addressed lymphedema and breast sensation. Using the patient's own tissues, several aesthetic refinements have led to optimizing the cosmetic appearance of the reconstructed breast. Implant‐based reconstruction has improved with the invention of form‐stable silicone implants, acellular dermal matrix, and fat grafting. These positive trends will continue into the future. We hope that all women with a diagnosis of breast cancer will have the option of a consultation with a reconstructive plastic surgeon, ideally prior to undergoing resective surgery, to ensure they are aware of all reconstructive options to maximize their reconstructive result.